PERHITUNGAN HARGA POKOK PRODUKSI CPO (CRUDE PALM OIL) PADA PT. SWAKARSA SINARSENTOSA DI SAMARINDA - Adi Suroso, Merisa Oktavia, Titin Ruliana (EKONOMIA, 2015)
PT. Swakarsa Sinarsentosa is a company engaged in the palm oil industry in the form of CPO (crude palm oil) and has several factories as a means of supporting the activities of the companies in the form of refined palm produce CPO. CPO was created as the main material for edible oil and also the use of palm oil as a cosmetic ingredient depends on the willingness of consumersTo determine the magnitude of the cost per tons CPO produced by PT. Swakarsa Sinarsentosa used basis for calculating the cost of production to by the company with the full costing method. Having in mind the cost of production is determined by the company with the full costing approach. It will show the difference of the two main components of the overall cost of goods and cost of goods per tons CPO.The purpose of this study was to determine differences in the calculation of the cost of production per tonne of CPO between the company according to the method of calculating the cost of production approach to full costing. Basic theory of management accounting used by using a method of analysis of the cost of production approach to full costing.Based on the analysis and discussion, the conclusions of this study as follows That the amount of the cost of production according to the calculations of PT Swakarsa Sinarsentosa Samarinda is smaller than the calculation of the treatment method of full costing. This means that there is a difference that should be correction. Cost of CPO by PT Swakarsa Sinarsentosa Samarinda is smaller than the calculation of the treatment method of full costing This means that there is a difference in the cost per ton of CPO. The difference is caused by differences in the calculation of the product is lost at the end of the process according to the PT Swakarsa Sinarsentosa. That consistent with the hypothesis put forward the hypothesis put forward is supposed that the calculation of the cost of production of CPO PT Swakarsa Sinarsentosa smaller when calculated using the cost method of production received full costing approach.